This Text Book Serves As a Guide for Readers Learning about the Technical Design of Intelligent Instruments, That Is, Instruments Designed to Collect Information about the Performance of Other Electronic Devices and Systems. the Book Introduces the Reader - Deng, Changjian (Bentham Science Publishers, 2020)
This text book serves as a guide for readers learning about the technical design of intelligent instruments, that is, instruments designed to collect information about the performance of other electronic devices and systems. The book introduces the readers to the concept of intelligent instrumentation and guides them on more advanced aspects of the subject including signal detection and analysis, data processing, performance analysis and data communication. Practical examples are also provided in the latter half of the book to blend the theoretical concepts with applied knowledge for the benef.